Second time's the charm - Morgan, Melissa J. (New York : Grosset & Dunlap, 2006)
Having returned for her second year at Camp Lakeview, Natalie finds herself feeling jealous of a new camper from California who seems to be even more sophisticated and glamorous that Natalie, herself.
Keywords: Jealousy -- Juvenile fiction; Camps -- Juvenile fiction; Friendship -- Juvenile fiction; Pennsylvania -- Juvenile fiction